2017
DOI: 10.1038/s41598-017-13727-z
|View full text |Cite|
|
Sign up to set email alerts
|

Region and species dependent mechanical properties of adolescent and young adult brain tissue

Abstract: Traumatic brain injuries, the leading cause of death and disability in children and young adults, are the result of a rapid acceleration or impact of the head. In recent years, a global effort to better understand the biomechanics of TBI has been undertaken, with many laboratories creating detailed computational models of the head and brain. For these models to produce realistic results they require accurate regional constitutive data for brain tissue. However, there are large differences in the mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 52 publications
5
65
0
Order By: Relevance
“…The dependence of signal stability on anatomical position may be related to inter-regional differences in the viscoelastic properties of nervous tissues and amount of tissue micromotion. Differences in tissue elasticity have been observed across different structures in the brain (MacManus et al, 2018) and between white and gray matter (Budday et al, 2015) , but a comparison between anterior and posterior cortex of the pig brain did not show a difference in elastic modulus (Gefen and Margulies, 2004) . It is therefore uncertain to what extent differences in elastic moduli of brain tissue could explain the dependence of the stability of spiking signals on the anatomical position.…”
Section: Long-term Stability Of Neural Signalsmentioning
confidence: 95%
See 1 more Smart Citation
“…The dependence of signal stability on anatomical position may be related to inter-regional differences in the viscoelastic properties of nervous tissues and amount of tissue micromotion. Differences in tissue elasticity have been observed across different structures in the brain (MacManus et al, 2018) and between white and gray matter (Budday et al, 2015) , but a comparison between anterior and posterior cortex of the pig brain did not show a difference in elastic modulus (Gefen and Margulies, 2004) . It is therefore uncertain to what extent differences in elastic moduli of brain tissue could explain the dependence of the stability of spiking signals on the anatomical position.…”
Section: Long-term Stability Of Neural Signalsmentioning
confidence: 95%
“…First, the long-term yield across different brain regions is unknown, because prior chronic studies recorded from a small set of brain regions using test-phase probes (Juavinett et al, 2019;Jun et al, 2017) . Because the brain is not mechanically isotropic, with different viscoelastic properties and levels of respiration-and cardiac-related movement in different regions (Bayly et al, 2005;Budday et al, 2015;MacManus et al, 2018;Sloots et al, 2020) , the stability of spiking signals is likely to vary across regions.…”
Section: Introductionmentioning
confidence: 99%
“…Measurements on intact brains rather than brain slices have also opposing results. For example, 12 weeks old mice were 13-59% stiffer than 6 weeks old mice [35] while immature rat brains (PND13 and PND17) were stiffer than mature ones (PND43 and PND90) [56]. Therefore, our study contributes to the body of evidence that brain tissue stiffens with maturation.…”
Section: Changes In Mechanical Properties Of the Hippocampus With Agementioning
confidence: 62%
“…During this process, the brain undergoes structural changes such as maturation of extracellular matrix (ECM), myelination, decrease in water content and cell number, dendritic pruning and synaptogenesis, all of which might be accompanied by mechanical alterations [29,30,31,32,33,34]. A majority of previous studies have already reported that stiffness increases with maturation [25,27,28,35], yet direct correlations with structural components of measured regions were never investigated. Therefore, the co-quantification of mechanical properties and the composition of the developing brain not only would shed light on structure-stiffness relationship of the brain but also on postnatal maturation of the brain.…”
Section: Introductionmentioning
confidence: 99%
“…39 Further, a study using micro-indentation TBI found that not only do different regions of the mouse, rat, or porcine brain respond differently to indentation, but, at ages ranging from 6-25 weeks old, younger brains rebound more quickly. 40 In contrast, the immature rat brain is stiffer than the adult brain, and the thickness of the adult skull and stiffness of the adolescent brain essentially counterbalance each other. 41 Thus, future studies should examine these characteristics in mice, particularly at such a close age difference, to determine if differences in skull and brain mechanics can explain the divergence in outcomes seen in this study.…”
Section: Discussionmentioning
confidence: 99%